Assessing financial access in Brazil - Kumar, Anjali, 1956- (World Bank working paper, 2005)
Access to financial services in Brazil has been relatively stable over the past ten years, despite the banking sector contraction of the late 1990s. Wide geographic variations in the supply of banking services by region and municipality are partly explained by differentials in income and population density. On a cross-country basis, Brazil does not appear to be underbanked. Looking at the use of financial services by different groups of consumers in Brazil, differences in financial access across regions is confirmed, but differences among richer and poorer neighborhoods can be as important. Public financial institutions in Brazil, deemed to be socially responsible, appear to have served disadvantaged groups more than private banks on some measures and for some services. However, their role varies by type of service, and in the case of some services, public banks in fact may have better served the better-off groups. At the level of individuals, the most important determinants of access to financial services are socio-economic characteristics such a income, wealth, and education. This may signify that in the presence of asymmetric information, access to such services depends critically on client information, and such characteristics provide a proxy for creditworthiness.